2016
DOI: 10.1016/j.jcrc.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The association between prior statin use and long-term outcomes after critical care admission

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…23 However, Beed et al reported that there was no association between previous statin use and survival outcome after ICU admission. 24 These studies did not consider the effects of different types of statins 25 or the daily dose. 15 Copyright © 2019, the American Society of Anesthesiologists, Inc.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, Beed et al reported that there was no association between previous statin use and survival outcome after ICU admission. 24 These studies did not consider the effects of different types of statins 25 or the daily dose. 15 Copyright © 2019, the American Society of Anesthesiologists, Inc.…”
Section: Discussionmentioning
confidence: 99%